2012
DOI: 10.1097/md.0b013e318277cf75
|View full text |Cite
|
Sign up to set email alerts
|

Familial Mediterranean Fever in Japan

Abstract: Familial Mediterranean fever (FMF) is a hereditary autoinflammatory disease that is prevalent in Mediterranean populations. While it is considered a rare disease in the rest of world, a significant number of FMF patients have been reported in East Asia, including Japan. Our aim was to determine the prevalence of FMF in Japan and elucidate the clinical and genetic features of Japanese patients. A primary nationwide survey of FMF was conducted between January and December 2009. Hospitals specializing in pediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
107
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 110 publications
(121 citation statements)
references
References 38 publications
8
107
1
5
Order By: Relevance
“…In a nationwide study in Japan, the mean period from disease onset to diagnosis was 9.1±9.3 years, thus suggesting a delay in diagnosis (2). In the present three cases, the mean period from disease onset to diagnosis was 24 months.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…In a nationwide study in Japan, the mean period from disease onset to diagnosis was 9.1±9.3 years, thus suggesting a delay in diagnosis (2). In the present three cases, the mean period from disease onset to diagnosis was 24 months.…”
Section: Discussionmentioning
confidence: 73%
“…In the nationwide study of FMF in Japan, the MEFV gene mutation was not identified in 17 of 126 patients (13.5%) (2). The present two patients without the MEFV gene mutation were the two elderly patients.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although many mutations have been reported, the most frequent mutations are located in exon 10 (M694V, M680I, V726A and M694I) and exon 2 (E148Q) (12). Migita et al reported that among 142 Japanese FMF patients, they found 12 carrying a heterozygous E84K mutation and four carrying a heterozygous G304 mutation who presented with a heterogeneous clinical phenotype (13). Meanwhile, Brucato et al searched for MEFV mutations confined to exon 10 (using direct sequencing) and exon 2 E148Q (by restriction site analysis) in 23 Italian IRP patients; however, they found no mutations (14).…”
Section: Discussionmentioning
confidence: 99%